Written press in the USARB Scientiﬁc Library collections (Confluenţe Bibliologice, 2015)
Bălţi university library collections are held about 3200 titles of magazines in 161 793 copies. Annual subscriptions are over 190 magazine and newspaper titles according to the faculties proﬁle and adjacent areas, published in Moldova, Romania, Russia, Ukraine, France, and USA. 41 titles in 850 copies of magazines is the collection of rare documents from the nineteenth century, early twentieth century. The magazines and newspapers are available on the Library website (http://libruniv.usarb.md) being an opportunity and advantageous for all users. Also, on the Web page can be accessed and viewed more than 58 214 on-line periodicals, oﬀered by 43 scientiﬁc databases, which are available through the Library Consortium Electronic Resources for Moldova (REM). The global provider EBSCOhost oﬀers 18 200 on-line magazines.
Keywords: periodicals; Rare periodical publications collection; databases